Substitution of Formal and Informal Home Care Service Use and Nursing Home Service Use: Health Outcomes, Decision-Making Preferences, and Implications for a Public Health Policy - Chen, Chia-Ching; Yamada, Tetsuji; Nakashima, Taeko; Chiu, I-Ming (Frontiers in Public Health, 2017)
Objectives: The purposes of this study are: (1) to empirically identify decision-making preferences of long-term healthcare use, especially informal and formal homecare service use; (2) to evaluate outcomes vs. costs based on substitutability of informal and formal homecare service use; and (3) to investigate health outcome disparity based on substitutability. Methodology and Data: The methods of ordinary least squares, a logit model and a bivariate probit model are used by controlling for socio-economic, demographic and physical/mental health factors to investigate outcomes and costs based substitutability of informal and formal healthcare use. The data comes from the 2013 Japanese Study of Aging and Retirement (JSTAR), which is designed by Keizai-Sangyo Kenkyu-jo, Hitotsubashi University, and the University of Tokyo. The JSTAR is a globally comparable data survey of the elderly. Results: There exists a complement relationship between the informal homecare and community-based formal homecare services, and the elasticity’s ranges from 0.18~0.22. These are reasonable results which show that unobservable factors are positively related to informal homecare and community-based formal homecare, but negatively related to nursing home services based on our bivariate probit model. Regarding healthcare outcome efficiency issue, the informal homecare is the best one among three types of elderly care: informal homecare, community-based formal homecare, and nursing home services. Health improvement/outcome of elderly with the informal homecare is heavier concentrated on informal homecare services than the elderly care services by community-based formal homecare and nursing homecare services. Conclusions: Policy makers need to address a diversity of health outcomes and efficiency of services based on providing services to elderly through resource allocation to the different types of long-term care. A provision of partial or full compensation for elderly care at home is recommendable and a viable option to improve their quality of lives.